Preventing ways to minimize probabilities of corruption in LNGOs in Iraq - Kakahama, Amanj Lateef (International Journal of Scientific Research and Management (IJSRM), 2019)
Purpose:  the fragile of economic and political situations, weakness and instability in any country is a potential suitable medium to create and develop corrupted environment. Corruption minimizes the opportunity to funding projects in corrupted working environment. Typically the traditional image of local none government organizations leads to trust them, meanwhile the possibility of conducting corruption in these organizations is not far away from the staff. For example some directors or supervisors cheat the staff and seduce them to burn rate acts to show progress in the project, some mangers want to involve the staff in corrupted acts. This research arranged to minimize the potential corruption opportunities in local none government organizations in Iraq. Methodology: quantitative methodology was implemented. 29 questions plus participants` comment were arranged to be answered within 15 to 20 minutes. The collected data is primary data about the local none government organization current administration and professional state in Iraq.Finding: Level of corruption could be noted in the local none government organizations and based on the collected data this corruption is result of: a) lack of comprehensive and professional code of conduct / internal policy and b) absent of best practice and international criteria in managing and producing organization issues at daily bases. Based on the participants feedbacks international none government organizations are recommended to support building professional work environment in the local none government organizations in Iraq.